Perwujudan Teknologi : Kontribusi Don Ihde Terhadap Filsafat Teknologi - Fitria Rayani Rahman; Intan Oktaviani Agustina; Yusuf Tri Herlambang (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Technological progress is developing very rapidly nowadays, of course it cannot be separated from the contribution of experts to the philosophy of technology, one of whom is Don Ihde. This research discusses changes in technology and Don Ihde's contribution to the Philosophy of Technology. This research method is qualitative through literature study in the form of published books and journals. The aim of this research is to find out what reproductions and contributions have been realized by Don Ihde. The method used in this research is literature study by reviewing and then analyzing several published books and journals to get an answer to a problem. The findings of this research are very necessary to provide an explanation of Don Ihde's contribution to the philosophy of technology. According to Don Ihde, humans cannot be separated from technology